2003
DOI: 10.1046/j.1439-0450.2003.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Herd Management Practices Associated with Paratuberculosis Seroprevalence in Dutch Dairy Herds

Abstract: We describe the paratuberculosis management practices applied in dairy herds in the Netherlands. The findings from paratuberculosis seronegative and seropositive herds were compared to discover possible risk factors. In total, 370 randomly selected herds with > or =20 dairy cows were surveyed. A questionnaire was used to collect data on current and previous paratuberculosis management practices. All cattle aged > or =3 years were serologically tested for paratuberculosis using an enzyme-linked immunosorbent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 17 publications
2
47
1
1
Order By: Relevance
“…Two previous studies also identified a significant positive association between culling of clinical or potentially clinical animals and herd/flock status and concluded that this practice was a consequence of higher losses, not a cause (Lugton, 2004;Muskens et al, 2003).…”
Section: Ojd-control Methodsmentioning
confidence: 91%
“…Two previous studies also identified a significant positive association between culling of clinical or potentially clinical animals and herd/flock status and concluded that this practice was a consequence of higher losses, not a cause (Lugton, 2004;Muskens et al, 2003).…”
Section: Ojd-control Methodsmentioning
confidence: 91%
“…In contrast, in a study conducted in the Netherlands, soil pH was not significantly different between seropositive and seronegative dairy cattle herds (Muskens et al, 2003). Moreover, the application of lime to the soil (to increase pH) appeared not to affect the survival of MAP in an Australian field trial (Whittington et al, 2004).…”
Section: Introductionmentioning
confidence: 76%
“…It has been demonstrated that the odds of being JD-positive is greater for larger herds than for smaller herds [30,38]. Furthermore, farms that purchase stock from other farms are more likely to be positive than farms that do not purchase stock (closed herds) [30,31].…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…However, the conventional herds were larger than the organic herds in this study. Commonly, larger herds have a higher JD prevalence than smaller herds [30,38]. Therefore, comparisons cannot easily be made without adjustments for herd size.…”
Section: Johne's Disease Prevalence On Organic Dairy Farmsmentioning
confidence: 99%